A case report of a giant mature teratoma of the thyroid gland in a young girl. Issue 9 (March 2019) - Lv, Zhibao; Bai, Xiaoling; Sheng, Qingfeng; Liu, Jiangbin; Wu, Yibo
Abstract: Rationale: Teratomas are extremely rare in the thyroid gland. A cervical teratoma presenting as a cystic or mixed thyroid lesion can be easily confused with a thyroglossal duct cyst. It is difficult for pediatricians to differentiate between these 2 types of lesions. Patients concerns: A 2-year-old girl who presented a growing thyroid mass for 14 months showed a mass in her left thyroid lobe under contrast-enhanced computed tomography (CT). Diagnosis and interventions: Ultrasonography found a mass of 5 × 3.5 cm within the left lobe of the thyroid gland, and the sonogram revealed areas with echo-free and mixed-echo patterns. There was no accumulation of technetium-99m pertechnetate on the thyroid scintigraphy (cold thyroid nodule). CT scan showed a mass (5.0 × 3.0 × 2.5 cm in size) that extended from the left thyroid lobe to the anterior mediastinum with no evident enhancement and clear margins that contained calcifications. Complete excision without intraoperative capsule disruption was achieved. Histologically, the thyroid mass was diagnosed as a mature teratoma. Outcomes: The postoperative course was uneventful after follow-ups for 2 years, and the patient had no inflammatory signs or evidence of recurrence. Lessons: Thyroid teratoma is rare in infants and is usually benign; however, some thyroid teratomas are malignant and inclined to relapse. The authors emphasize that thyroid teratomas in children should be included in the differential diagnosis of cystic lesions located in the head and neck area. Complete resection is essential for good outcomes. In addition, long-term follow-ups are warranted to follow the complications of the malignant or recurrent disease.